Efektivitas Pengamanan Aset Tetap Tanah Pada Pemerintah Kota Bandung - Rahayu, Asri Puji; Muhammad, Rahma Nazila (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The purpose of this study is to determine the effectiveness of securing land fixed assets as well as the inhibiting factors and efforts to overcome the problem of securing land fixed assets in Bandung City Government. The type of research used in this research is qualitative with a descriptive approach. The data collection method used was interviews and well as documentation. The results of the study show that the Bandung City Government carries out safeguards for land fixed assets in accordance with applicable laws even though there are still obstacles caused by incomplete documents and a lack of human. Based on the effectiveness analysis using Campbell's theory, it is known that in terms of program success, program satisfaction, input and output levels as well as the indicators of achievement of overall goals have been effective. However, the indicators of target success have not been effective. The Bandung City Government resolves existing problems with physical control, synergizes with relevant agencies and periodic censuses